(untitled) (Contemporary Journal of Social Science Review, 2025)
The rapid advancement of Artificial Intelligence (AI) is transforming multiple facets of society, including the legal profession and, more specifically, judicial decision-making. AI technologies—ranging from predictive analytics and natural language processing to machine learning algorithms—are increasingly being employed in courts to assist in legal research, case prediction, sentencing guidelines, and workload management. This article explores the evolving role of AI in judicial processes through a comparative legal analysis across developed and developing jurisdictions. While AI promises efficiency, consistency, and transparency in judicial outcomes, it simultaneously raises critical concerns regarding accountability, bias, interpretability, and the preservation of judicial independence. The study argues that although AI can enhance judicial decision-making, its integration must be guided by strict ethical frameworks, robust legal safeguards, and transparent policies to prevent misuse. Ultimately, the comparative perspective highlights that AI is not a replacement for human judges but rather a supportive tool that, if regulated properly, can strengthen justice systems worldwide.